Industry 5.0 Innovations for Waste Management and Circular Economy in Sustainable Food systems: A systematic review - Gaikwad Snehal; Anerao Kishor (BIO Web of Conferences)
The transformation of sustainable food systems demands innovative waste management approaches and circular economy practices. The adoption of Industry 5.0 technologies contributes towards aligning with the recent advancements for sustainable food systems. Industry 5.0, characterized by human-centric automation, artificial intelligence (AI), Internet of Things (IoT), and advanced robotics, extends impactful solutions to enhance efficiency, reduce waste, and promote sustainability in food supply chains. This systematic review delves the role of Industry 5.0 technologies in optimizing waste management and fostering circular economy principles within the food sector. The study synthesizes cutting-edge technologies, focusing on smart waste monitoring, precision resource recovery, AI-driven food waste reduction, and blockchain-enabled traceability, cloud computing and 3D-printing of food waste recovery to valuable edible products. Findings indicate that collaboration of Industry 5.0 innovations can significantly minimize food loss, enhance upcycling and valorization of by-products, and support sustainable production-consumption loops. However, challenges to tackle include high implementation costs, regulatory barriers, and technological adoption gaps persist. Future research should manage the policy frameworks, scalable solutions, and cross-sectoral collaboration to maximize the potential of Industry 5.0 in achieving sustainable food systems.